PROPOSED MARKETING STRATEGY FOR MOBILE PAYMENT TO INCREASE USER OF T-MONEY (STUDY CASE: T-MONEY) - Fadhlih, Adri
T-money is a mobile application platform launched by Telkom, which aims to help the community to provide transaction of payments and purchases with a mobile phone. At the time T-money was in the form of smart card that using RFID technology. As the time goes by, T-money evolved as financial technology that can used with mobile phone and tablet. T-money users can save their money in T-money application as their balance for all transaction. T-money can be used by all mobile operators. The technology of T-money for purchasing is by using QR code. T-money has 2 types of services, basic service and full service. T-money business issues are, there were lack of active T-money users and usage. However, they try to increase the number of users by promoting directly or door to door strategy to those who need financial platform such as SME, companies and even the government. The theoretical approach that used to solve this issues is using general environment (PEST), industry environment (Porter’s 5 force), competitor analysis, customer analysis, resource, capabilities and value chain analysis. After collecting and processing the data then proceed to SWOT analysis to obtain the strength, weakness, opportunity, and threat. Business issues in this research found that many competitors are high substitution as new entrants of financial mobile application and less product of differentiation. From the results of SWOT analysis obtained, then proceed to TOWS analysis to obtain the solutions. By considering the results of previous analysis this research acquired the marketing strategy to develop segmenting, targeting and positioning, and marketing mix. The implementation section included the activity timeline plan and budgeting plan. Proposed the segmentation to all generation that using mobile operator. Proposed targeting user is market penetration to other financial application subscribers and to all mobile operators to be T-money user. Proposed positioning T-money is an easy to use, easy understand, and safe to use with this application with innovative technology and unique features for transaction by mobile phone. Proposed marketing mix to develop their product with new feature, collaborate with E-commerce, develop user interface, update offline and online merchants. Promotion by using YouTube and Instagram, Discount reminder, T-money food & SME fest. Place by expend the new branch